Professional legal culture, its content and role in the further civilized development of Ukraine - Ткачова, Н. О. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In this article an attempt is made to investigate the problematic issues of methodology, contents and significanceof the contemporary specialist social phenomenal formation that is of vocational and legal education, which has not yet been complex studied neither at the juridical not at the psychological or pedagogical levels.